Genetics : - Pierce, Benjamin A. (W.H. Freeman, 2008)
The updated third edition builds upon the features that have made past editions so successful: an engaging writing style; relevant applications; an accessible and instructive art program; an emphasis on problem-solving; and, most importantly, a strong focus on concepts and connections.